N, P‐Codoped Carbon Networks as Efficient Metal‐free Bifunctional Catalysts for Oxygen Reduction and Hydrogen Evolution Reactions. (28th December 2015) - Zhang, Jintao; Qu, Liangti; Shi, Gaoquan; Liu, Jiangyong; Chen, Jianfeng; Dai, Liming
Abstract: The high cost and scarcity of noble metal catalysts, such as Pt, have hindered the hydrogen production from electrochemical water splitting, the oxygen reduction in fuel cells and batteries. Herein, we developed a simple template‐free approach to three‐dimensional porous carbon networks codoped with nitrogen and phosphorus by pyrolysis of a supermolecular aggregate of self‐assembled melamine, phytic acid, and graphene oxide (MPSA/GO). The pyrolyzed MPSA/GO acted as the first metal‐free bifunctional catalyst with high activities for both oxygen reduction and hydrogen evolution. Zn–air batteries with the pyrolyzed MPSA/GO air electrode showed a high peak power density (310 W g −1 ) and an excellent durability. Thus, the pyrolyzed MPSA/GO is a promising bifunctional catalyst for renewable energy technologies, particularly regenerative fuel cells.